Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Get the answers you need quickly and accurately from a dedicated community of experts on our Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Absolutely, let's break down the original expression step by step:
The given expression is:
[tex]\[ 2 \sqrt{27} + \sqrt{12} - 3 \sqrt{3} - 2 \sqrt{12} \][/tex]
First, let's simplify each square root term individually:
1. \( \sqrt{27} \) can be simplified as:
[tex]\[ \sqrt{27} = \sqrt{9 \cdot 3} = \sqrt{9} \cdot \sqrt{3} = 3 \sqrt{3} \][/tex]
Therefore,
[tex]\[ 2 \sqrt{27} = 2 \cdot 3 \sqrt{3} = 6 \sqrt{3} \][/tex]
2. \( \sqrt{12} \) can be simplified as:
[tex]\[ \sqrt{12} = \sqrt{4 \cdot 3} = \sqrt{4} \cdot \sqrt{3} = 2 \sqrt{3} \][/tex]
3. Therefore:
[tex]\[ 2 \sqrt{12} = 2 \cdot 2 \sqrt{3} = 4 \sqrt{3} \][/tex]
Substituting these simplified terms back into the original expression, we get:
[tex]\[ 6 \sqrt{3} + 2 \sqrt{3} - 3 \sqrt{3} - 4 \sqrt{3} \][/tex]
Now, let's combine like terms:
[tex]\[ 6 \sqrt{3} + 2 \sqrt{3} - 3 \sqrt{3} - 4 \sqrt{3} \][/tex]
Combine coefficients of \( \sqrt{3} \):
[tex]\[ (6 + 2 - 3 - 4) \sqrt{3} = 1 \sqrt{3} \][/tex]
So, the simplified form of the expression is:
[tex]\[ \sqrt{3} \][/tex]
Thus, the correct choice is:
[tex]\[ \sqrt{3} \][/tex]
The given expression is:
[tex]\[ 2 \sqrt{27} + \sqrt{12} - 3 \sqrt{3} - 2 \sqrt{12} \][/tex]
First, let's simplify each square root term individually:
1. \( \sqrt{27} \) can be simplified as:
[tex]\[ \sqrt{27} = \sqrt{9 \cdot 3} = \sqrt{9} \cdot \sqrt{3} = 3 \sqrt{3} \][/tex]
Therefore,
[tex]\[ 2 \sqrt{27} = 2 \cdot 3 \sqrt{3} = 6 \sqrt{3} \][/tex]
2. \( \sqrt{12} \) can be simplified as:
[tex]\[ \sqrt{12} = \sqrt{4 \cdot 3} = \sqrt{4} \cdot \sqrt{3} = 2 \sqrt{3} \][/tex]
3. Therefore:
[tex]\[ 2 \sqrt{12} = 2 \cdot 2 \sqrt{3} = 4 \sqrt{3} \][/tex]
Substituting these simplified terms back into the original expression, we get:
[tex]\[ 6 \sqrt{3} + 2 \sqrt{3} - 3 \sqrt{3} - 4 \sqrt{3} \][/tex]
Now, let's combine like terms:
[tex]\[ 6 \sqrt{3} + 2 \sqrt{3} - 3 \sqrt{3} - 4 \sqrt{3} \][/tex]
Combine coefficients of \( \sqrt{3} \):
[tex]\[ (6 + 2 - 3 - 4) \sqrt{3} = 1 \sqrt{3} \][/tex]
So, the simplified form of the expression is:
[tex]\[ \sqrt{3} \][/tex]
Thus, the correct choice is:
[tex]\[ \sqrt{3} \][/tex]
We hope this was helpful. Please come back whenever you need more information or answers to your queries. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.